Exploring Emotional and Mental Health Challenges among Frontline Healthcare Workers during the COVID-19 Pandemic: A Qualitative Phenomenological Study - Danjuma Aliyu (The Nursing Scope, 2026)
Background: The COVID-19 pandemic placed frontline healthcare workers (FHCWs) under unprecedented emotional and psychological strain due to the heightened risk of infection, increased workload, prolonged working hours, and limited healthcare resources. In low- and middle-income countries such as Nigeria, these challenges were further compounded by inadequate institutional support and social stigma, underscoring the need to understand the lived experiences of healthcare workers during the pandemic. Aim: This study explored the lived experiences of frontline healthcare workers regarding the emotional and mental health challenges encountered while providing care at the COVID-19 isolation centre of Ahmadu Bello University Teaching Hospital, Zaria, Nigeria. Method: A qualitative phenomenological design was employed to gain an in-depth understanding of participants' experiences. Eleven frontline healthcare workers were purposively selected and participated in in-depth, semi-structured interviews. Interviews were audio-recorded, transcribed verbatim, and analysed using thematic analysis to identify recurrent patterns and themes related to participants' emotional and psychological experiences. Findings: Six major themes emerged from the analysis: emotional distress (fear of infection, anxiety, stress, and burnout); stigma and discrimination (social rejection and isolation); coping strategies (resilience, peer support, and spirituality); occupational challenges (long working hours, inadequate personal protective equipment, and increased workload); support systems (family, colleagues, and organisational assistance); and psychological consequences (depression, sleep disturbances, and diminished motivation). Participants also proposed recommendations for strengthening mental health services, capacity building, and policy support. Participants reported persistent psychological distress and social isolation while relying largely on informal coping mechanisms because structured psychological support services were limited. Conclusion: Frontline healthcare workers experienced considerable emotional and psychological challenges during the COVID-19 pandemic, driven by occupational stressors, fear of infection, stigma, and inadequate institutional mental health support. These experiences highlight the importance of integrating mental health protection into emergency preparedness and healthcare workforce management. Recommendation: Healthcare institutions and policymakers should establish comprehensive mental health support programmes, strengthen organisational and psychosocial support systems, improve access to adequate resources, and implement resilience-building interventions to safeguard frontline healthcare workers during future public health emergencies. Keywords: COVID-19; frontline healthcare workers; emotional distress; mental health; phenomenology; qualitative research.